PROFIL KEMAMPUAN BERADAPTASI DAN BERKOMUNIKASI MAHASISWA PROGRAM STUDI PENDIDIKAN TEKNIK BANGUNAN - Fajri Surya Helmi; Azwar Inra (Jurnal Applied Science in Civil Engineering, 2021)
This research aims to uncover the categories of ownership of adaptability and communication of PLK students of the Padang State University Building Engineering Education Study Program in 2020. This type of research is descriptive research with a quantitative approach. The population of this study is all productive teachers in SMK N 2 Solok which numbers 54 people. The sampling technique in this study uses total sampling that makes the entire population as a sample. The data collection technique in this study is to use questionnaires arranged on the likert scale and given to productive teachers in SMK N 2 Solok. Based on the results of the study can be concluded that the ability to communicate and adapt that students have is in the low category.